Effect of core-dependent loss on the intercore crosstalk in multicore fiber systems with concatenated random loss fiber segments - Rebola, J. L.; Cartaxo, A. V. T. (2023 23rd International Conference on Transparent Optical Networks (ICTON), 2023)
We investigate the impact of core-dependent loss (CDL) on the signal and crosstalk (XT) powers at the output of a link composed by several concatenated multicore fiber (MCF) segments, by considering random CDL in each MCF segment. We show that, with random CDL, for a 100 km optical link and specific arrangements of MCF segments, the forward, signal, coupled and direct XT powers may increase around 1 dB (with respect to the absence of CDL). We show also that, at the output of the concatenated MCF segments, the probability density functions of these powers follow a Gaussian distribution with random CDL generated from different statistical distributions.